Examining the Impact of Water and Energy Consumption Disclosure on Firm Value: A Case Study of The Vietnam Food and Manufacturing Sector - Pham Thi Thuy Hang; Nguyen Minh Thu; Nguyen Thi Minh Anh; Nguyen Thi Thanh Hang; Le Do Thanh Cong; Truong Duc Thanh Dat (My University, 2023)
Examining the Impact of Water and Energy Consumption Disclosure on Firm Value: A Case Study of The Vietnam Food and Manufacturing Sector
Keywords: Water disclosure